2009
DOI: 10.1345/aph.1m457
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib-Induced Hepatic Encephalopathy

Abstract: The multikinase inhibitorsorafenibwas recentlyapproved inEurope forthetreatment of advanced hepatic carcinoma (AHC). We reporta case of hepaticencephalopathy inducedby sorafenib,with positive rechallenge. Case Report. A 63-year-old patientwasdiagnosed with AHCassociated with Child-Pugh Class A alcohol-relatedcirrhosis (prothrombin 61%; bilirubin 13 mg/dL,albumin 2.9 g/dL,no ascitesor encephalopathy).There was no portalthrombosis and the patienthad not used alcohol since 2006. Chronic medical therapy consisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…reported another isolated case of sorafenib‐induced encephalopathy in a patient with advanced hepatocellular carcinoma. The encephalopathy resolved when sorafenib was withheld but then recurred when the drug was recommenced . The underlying mechanism of encephalopathy remained unclear, but in light of similar presentation, it was reasonably suspected to be a result of a class effect of these TKIs .…”
Section: Case Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported another isolated case of sorafenib‐induced encephalopathy in a patient with advanced hepatocellular carcinoma. The encephalopathy resolved when sorafenib was withheld but then recurred when the drug was recommenced . The underlying mechanism of encephalopathy remained unclear, but in light of similar presentation, it was reasonably suspected to be a result of a class effect of these TKIs .…”
Section: Case Discussionmentioning
confidence: 99%
“…9 The authors of the case series suspected that sorafenib may have direct neuronal action, which could have triggered the onset of metabolic encephalopathy. 9 Marks et al 10 reported another isolated case of sorafenib-induced encephalopathy in a patient with advanced hepatocellular carcinoma. The encephalopathy resolved when sorafenib was withheld but then recurred when the drug was recommenced.…”
Section: Case Discussionmentioning
confidence: 99%
“…In these case reports and in a third report involving a closely related drug, sorafenib, drug discontinuation leads to resolution of elevated ammonia levels. 6,7 Our patient had HCC without portal hypertension and had intact hepatic synthetic function. The patient's age and lack of prior symptoms made the possibility of a dominant genetic disorder such as OTC deficiency extremely small.…”
Section: Commentmentioning
confidence: 85%
“…First, the possible associations between hepatic encephalopathy and sorafenib have been reported, [3][4][5] and there have recently been several cases of serious adverse events leading to death. Furthermore, hepatic encephalopathy was reported in 34 of 2375 (1.4%) in Japanese patients in a blue letter by Bayer, which was higher than that in other countries.…”
Section: Discussionmentioning
confidence: 99%